Common cathode VCSEL driver in 90 nm CMOS enabling 25 Gbit/s optical connection using 14 Gbit/s 850 nm VCSEL. Issue 4 (1st February 2015) - Belfiore, G.; Szilagyi, L.; Henker, R.; Ellinger, F.
Abstract : The design and electro‐optical measurements of a 25 Gbit/s common cathode vertical cavity surface‐emitting laser (VCSEL) driver in 90 nm bulk CMOS technology is presented. The driver is bonded to a 14 Gbit/s commercial VCSEL providing both DC and modulation current to the laser. The power consumption including the VCSEL is 60 mW. Since the DC bias of the VCSEL exceeds the breakdown voltage of thin oxide transistors, a novel output stage configuration using isolated wells is proposed. The active area is only 127 × 50 μm.